The Impact of tourism on the socio-cultural setting of rural communities in Ghana "a case study of Boabeg-fiema in the Brong Ahafo region" - Tamakloe, Geoffrey deladem (KDI School, 2011)
There is the need to analyse and understand the impacts of tourism with an orientation to reducing the negative impacts and reinforcing the positives. In Ghana, adequate economic analysis of tourism has been carried out to determine its contribution to GDP, however, little has been done to assess the socio-cultural impacts of tourism on host communities. In view of this, the study sought to examine the impacts of tourism from the socio-cultural perspective in tourism host communities with specific focus on the Boabeng-Fiema in the Brong Ahafo region of Ghana. Qualitative data obtained from structured questionnaires and in-depth interviews were the main source of input for analyses. The study concluded that the socio-cultural impacts of tourism on host communities are mixed, and that tourism largely affects the socio-cultural setting of local communities. The study recommended that management of the tourism industry must plan policies to reinforce the positive impacts of tourism and try to mitigate the negative impacts with the involvement of host communities so that residents understand tourism industry. It was also recommended the host communities should participate in the decision making process and receive benefits from the industry.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Ghana